Analysis of the in vitro and in vivo effects of photodynamic therapy on prostate cancer by using new photosensitizers, protoporphyrin IX-polyamine derivatives - Fidanzi-Dugas, Chloë; Liagre, Bertrand; Chemin, Guillaume; Perraud, Aurélie; Carrion, Claire; Couquet, Claude-Yves; Granet, Robert; Sol, Vincent; Léger, David Yannick (Biochimica et biophysica acta. General subjects, 2017)
Photodynamic therapy, using porphyrins as photosensitizers (PS), has been approved in treatment of several solid tumors. However, commonly used PS induce death but also resistance pathways in cancer cells and an alteration of surrounding normal tissues. Because polyamines (PA) are actively accumulated in cancer cells by the Polyamine Transport System (PTS), they may enable PS to specifically target cancer cells. Here, we investigated whether new protoporphyrin IX-polyamine derivatives were effective PS against prostate cancer and whether PA increased PDT specificity after 630nm irradiation. CHO and CHO-MG cells (differing in their PTS activity) were used to assess efficacy of polyamine vectorization. MTT assays were performed on human prostate non-malignant (RWPE-1) and malignant (PC-3, DU 145 and LNCaP) cell lines to test PS phototoxicity. ROS generation, DNA fragmentation and cell signalling were assessed by ELISA/EIA, western-blots and gel shift assays. Finally, PS effects were studied on tumor growth in nude mice. Our PS were more effective on cancer cells compared to non-malignant cells and more effective than PpIX alone. PpIX-PA generated ROS production involved in induction of apoptotic intrinsic pathways. Different pathways involved in apoptosis resistance were studied: PS inhibited Bcl-2, Akt, and NF-κB but activated p38/COX-2/PGE2 pathways which were not implicated in apoptosis resistance in our model. In vivo experiments showed PpIX-PA efficacy was greater than results obtained with PpIX. All together, our results showed that PpIX-PA exerted its maximum effects without activating resistance pathways and appears to be a good candidate for prostate cancer PDT treatment. [Display omitted] •New photosensitizers were synthesized: Protoporphyrin IX (PpIX) was coupled with polyamines•Polyamines enhanced PpIX efficiency and targeted cancer cells•In vitro, photoactivated photosensitizers induced apoptotic intrinsic pathway by ROS production•Pathways known as inducer of apoptosis resistance were not activated•Photosensitizers in vivo efficiency was shown on nude mice xenografts